Prodigiosin induced the caspase-dependent apoptosis in human chronic myelogenous leukemia K562 cell - Maryam Niakani; Ahmad Majd; Parviz Pakzad; Hassan Malekinejad (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Chronic myeloid leukemia (CML) as a myeloproliferative disease is characterized by increased cellularity of bone marrow. Implementing the latest treatment protocols is currently accompanied by serious and life-threatening side effects. There are worldwide attempts to find new effective and potent therapeutic agents with minimal side effects on CML patients. This in vitro study was carried out to discover the potential antiproliferative and apoptotic effects of naturally produced prodigiosin (PDG) on K562 cells as an accepted model of CML. Experimental approach: The anti-proliferative effect of PDG was measured by MTT assay. To highlight the mechanism of cytotoxicity, the apoptotic cell death pathway was investigated by morphological and biochemical assessments. The dual acridine orange/ethidium bromide staining technique and western blotting method were applied to assess the mechanism of the potential apoptotic impact of PDG on K562 cells. Findings/Results: PDG-induced time- and concentration-dependent anti-proliferative effects were revealed with an estimated IC50 value of 54.06 μM. The highest cell viability reduction (60%) was recorded in cells, which were exposed to 100 μM concentration. Further assays demonstrated that in the dual acridine orange/ethidium bromide staining method the cell population in the late apoptosis phase was increased in a concentration-dependent manner, which was confirmed with remarkable DNA fragmentation. Conclusion and implications: We found that the PDG-induced apoptosis in K562 cells is mediated through the caspase-3 activation both in mRNA and protein levels. Our results suggest that PDG could be a potent compound for further pharmacokinetic and pharmacodynamics studies in the in vivo model of CML.